Perampanel Inhibits α‐Synuclein Transmission in Parkinson's Disease Models. Issue 7 (4th April 2021) - Ueda, Jun; Uemura, Norihito; Sawamura, Masanori; Taguchi, Tomoyuki; Ikuno, Masashi; Kaji, Seiji; Taruno, Yosuke; Matsuzawa, Shuichi; Yamakado, Hodaka; Takahashi, Ryosuke
Abstract: Background: The intercellular transmission of pathogenic proteins plays a key role in the clinicopathological progression of neurodegenerative diseases. Previous studies have demonstrated that this uptake and release process is regulated by neuronal activity. Objective: The objective of this study was to examine the effect of perampanel, an antiepileptic drug, on α‐synuclein transmission in cultured cells and mouse models of Parkinson's disease. Methods: Mouse primary hippocampal neurons were transduced with α‐synuclein preformed fibrils to examine the effect of perampanel on the development of α‐synuclein pathology and its mechanisms of action. An α‐synuclein preformed fibril‐injected mouse model was used to validate the effect of oral administration of perampanel on the α‐synuclein pathology in vivo. Results: Perampanel inhibited the development of α‐synuclein pathology in mouse hippocampal neurons transduced with α‐synuclein preformed fibrils. Interestingly, perampanel blocked the neuronal uptake of α‐synuclein preformed fibrils by inhibiting macropinocytosis in a neuronal activity‐dependent manner. We confirmed that oral administration of perampanel ameliorated the development of α‐synuclein pathology in wild‐type mice inoculated with α‐synuclein preformed fibrils. Conclusion: Modulation of neuronal activity could be a promising therapeutic target for Parkinson's disease, and perampanel could be a novel disease‐modifying drug for Parkinson's disease. © 2021 International Parkinson and Movement Disorder Society